PAKISTAN’S FOREIGN AND PUBLIC POLICY TOWARDS USA: A CASE OF BUSINESS IMPLICATIONS (2000 TO ONWARDS) (Contemporary Journal of Social Science Review, 2025)
Pakistan's foreign policy toward the United States (USA)reflects a strategic balancing act, shaped by shifting global power dynamics and domestic economic imperatives. While Pakistan’s alliance with the USA has largely revolved around counterterrorism, military aid, and security cooperation post-9/11, this relationship has been marred by trust deficits and conditional assistance. This study examines Pakistan's foreign and public policy towards the United States from 2000 to onwards, with a focus on its economic and business implications. The analysis delves into the bilateral relationship shaped by counterterrorism efforts, strategic alliances, and shifting geopolitical priorities. It highlights the economic impacts of U.S. aid, trade agreements, and diplomatic engagements on Pakistan’s economy while addressing the challenges of dependency, policy contradictions, and public perceptions. The research underscores the interplay between economic policies and broader geopolitical strategies, offering insights into the complexities of Pakistan’s foreign relations and economic outcomes in a globalized context.